A Protein Microarray-Based Investigation of Cerebrospinal Fluid Reveals Distinct Autoantibody Signature in Low and High-Grade Gliomas - Gahoi, Nikita; Syed, Parvez; Choudhary, Saket; Epari, Sridhar; Moiyadi, Aliasgar; Varma, Santosh G.; Gandhi, Mayuri N.; Srivastava, Sanjeeva (Frontiers in Oncology, 2020)
Gliomas are one of the most aggressive primary brain tumors arising from neural progenitor cells. Delayed diagnosis, invasive biopsy and diagnostic challenges stems the need for specific, minimally-invasive and early diagnostic biomarkers. Tumor-associated (TA) autoantibodies are measurable in the biofluids long before the onset of the symptoms, suggesting their role in early diagnosis and clinical management of the patients. In the current study, cerebrospinal fluid (CSF) samples from patients with low-grade gliomas (LGG) and the Glioblastoma multiforme (GBM) that characterizes advanced disease were compared with healthy control samples to identify putative TA Autoantibodies, using protein microarrays. The CSF samples from LGGs (n=10), GBM (n=7) were compared with the control CSF samples (n=6). Proteins showing significant antigenic response were further manually cross-verified. Proteins NOL4 (a cancer-testis antigen) and KALRN showed an antigenic response in the CSF of GBM patients, whereas, UTP4 and CCDC28A showed an antigenic response in low-grade gliomas when compared with the control samples. TA autoantibodies identified in this study from the CSF of the patients could supplement current screening modalities. Further, validation of these TA autoantibodies on a larger clinical cohort could provide cues towards relevance of these proteins in early diagnosis of the disease.